Analisis Potensi Curcumin Kunyit (Curcuma longa) Sebagai Agen Neuroproktektor, Antiinflamasi, dan Antioksidan: Inovasi Pengembangan Terapi yang Efektif pada Penderita Alzheimer - Surya Wijaya; Muthmainnah Arifin (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2012)
ABSTRACT Alzheimer is the most common type of dementia disorders affecting people all over the world. Alzheimer not only contribute to complications, disability, and high mortality rate, but also has implications in psychiatry and economic aspects. Unfortunately, until now there is no medical management to treat Alzheimer effectively. One of the herbs that is used as Alzheimer therapy is turmeric (Ctercuma longa) with its main components, curcumin. The aim of paper writing is to investigate the mechanism and potential applications of turmeric's curcumin as innovative therapy for Alzheimer patient. Data collection methods is literature study. whereas data analysis method is inductive. Curcumin has potential as management modality of Alzheimer because it serves as a neuroprotective agent by inhibiting the formation protein ? -arnyloid and tau protein cycle, decreasing the activity of ? -secretase and acetilcolinesterase, and antidislipidemia. Curcumin also acts as an anti-inflammatory agent through inhibition of NF-kB activity, COX-2, lipooxygenase, AP-1, iNOS, and Egr-1. In addition to these two effects, curcumin also has potential as an antioxidant agent through lowering activity of peroxidase, reactive oxygen species (ROS) and oxidative stress induced by homocysteine. This suggests that turmeric's curcumin has strong potential for fluffier development into alternative Alzheimer therapies.